Estimación de un índice de condiciones financieras para México - Thelma Armendáriz Villarreal; Claudia Ramírez Bulos (Banco de México, 2015)
– A tool that has been widely used to identify the state of financial conditions in a country are the financial conditions indexes, since they synthesize information from different variables in a single indicator allowing to identify the general behavior of financial conditions in a timely and condensed manner. In this paper we construct and analyze a Financial Conditions Index (FCI) for Mexico that allows to capture diverse episodes of financial stress and to know the main factors behind movements in financial conditions. The results show that this FCI adequately captures moments of astringency in financial markets in Mexico such as the financial crisis of 2008-2009, the crisis in Europe in mid-2011, the beginning of the "tapering talk" in the United States in the second half of 2013, among others. Keywords: Financial conditions index, principal components, Mexico
Keywords: G1; G10; G14; G15; G19; 330; financial conditions index; principal components; Mexico